Aspecte practice privind sistemul public de protecție a copiilor cu dizabilități - Bonea, Georgiana-Virginia (Calitatea Vieții, 2011)
Children with disabilities are not handicapped by definition, but children with special needs, who need be understood, not classified. Placement centers for children in Romania are constantly changing, but this work does not necessarily means the enhanced quality of the services provided for them. The system of social protection in Romania after twenty years of transition is still rudimentary and does not meet the needs of persons with disabilities. Also there is the need of an advice service for parents who have a child with disabilities in order to inform and support them. A child with a disability is two times more vulnerable and more sensitive than an adult with disabilities because he/she is more prone to judgments of the other children, who sometimes can be very hard on those who are different. A child generally needs protection, love, support, approval, encouragement and attention, but the child with disabilities needs to know that is not rejected, marginalized, due to his special needs. In the new penal code which is open to public debate, are violeted the fundamental human rights, allowing the tests on people with mental disabilities who can not express a valid agreement for the progress of science. Disability does not define the soul or mind, but it defines those using this as a label.